Managing Agricultural Production Through Vulnerability Study - Ujjwal Kumar (Indian Journal of Extension Education, 2017)
Agricultural vulnerability index is a tool for assessing vulnerability to various factors and is helpful in formulation ofadaptation strategies to cope up with adverse impact of biological and physical factors. Agricultural vulnerability isdependent upon climatic, biological, social and infrastructural factors. The study was conducted in Madhubani and Patnadistricts situated in north and south Bihar respectively. In each district three villages in three different blocks with variedagro-ecological conditions were selected for the study. Focus Group Discussion (FGD) technique was adopted for gettinginformation related to impact of biotic and abiotic factors. Total 36 FGDs consisting of male, female and mix group wereconducted in 6 villages in both districts.Among the climatic factors, drought during different stages of crop growth, flood /water logging, and heat stress are thought to be adversely affecting the farming practices which are more or less recurrentin Madhubani and Patna. Farmers are sometimes also affected by erratic nature of rainfall. All the villages under study areseverely to moderately affect by the disease, insect-pest or weeds. Among the social and technical factors, non-availabilityof quality inputs, manpower (especially, during peak period demand) and machinery are the most limiting factors forachieving desired level of yield. Agricultural vulnerability index was analyzed medium in both districts; while it was low(0.28 to 0.31) in two villages (one each in Madhubani and Patna districts). Villages with low vulnerability have lesser riskand lesser chance of failure of agricultural production. Agricultural vulnerability index in rest four villages varied from0.36 to 0.48 that revealed medium vulnerability. In such villages one should adopt technologies, crops and strategieswhich can minimize risk from adverse climatic, social and biological factors for higher productivity